MIGA Annual Report 2014 : Insuring Investments, Ensuring Opportunities - Multilateral Investment Guarantee Agency (Washington, DC: World Bank Group, 2014)
In 2014, the World Bank Group adopted a joint strategy for dealing with impediments to ending extreme poverty and boosting shared prosperity. One of the strategy’s key elements underscores the essential role private sector investment can play working alongside public sector support to bear down on the most challenging development issues client countries face, such as job creation, infrastructure deficits, and climate change. MIGA’s role has become increasingly valuable in delivering results to achieve these twin goals as demonstrated by the increased demand for our political risk insurance and credit enhancement products that facilitate the expansion of private investment into emerging markets. In fiscal year 2014, MIGA issued a record $3.2 billion in new guarantees while our gross exposure reached $12.4 billion. MIGA’s added value stems from our ability to mobilize private sector investment in environments that are often beyond the risk tolerance of commercial sources of capital. This past fiscal year, MIGA worked with various stakeholders to develop our own strategy that aligns our objectives with the World Bank Group’s twin goals and underscores our aspiration to achieve significant development impact beyond what we can do alone. To achieve this, MIGA will need to be financially sustainable by prudently managing our risks, covering operating costs, and creating financial latitude by growing the Agency’s capital base.